Clinical efficacy of ultra-laser irradiation combined with gabapentin on elderly patients with cervical spondylotic radiculopathy - Yu, Zhou; Sun, Haoliang; Liu, Xin (Frontiers in Neurology, 2025)
ObjectiveCervical spondylotic radiculopathy is the most prevalent form of cervical spondylosis. This study aimed to investigate the clinical efficacy of ultra-laser irradiation combined with gabapentin for treating elderly patients with cervical spondylotic radiculopathy, providing a basis for optimizing treatment strategies.MethodsIn this single-blind randomized controlled trial, 160 elderly patients diagnosed at our hospital from March to June 2025 were assigned (1:1) to ultra-laser irradiation plus gabapentin or gabapentin alone (80 per group). Pain was assessed with the Numerical Rating Scale (NRS) and health status with the EQ-5D at baseline and after three courses of treatment (30 sessions in total). Adverse events were recorded.ResultsBaseline NRS scores were similar between groups. After treatment, the between-group difference in NRS improvement was 1.90 points (95% CI 1.64–2.16; p < 0.001) favoring the combination. The between-group difference in EQ-5D change was 0.08 (95% CI 0.04–0.12; p < 0.001). Patients who experienced at least one adverse event accounted for 12.5% (10/80) in the combination group and 42.5% (34/80) in the gabapentin-only group (χ2 = 18.06, p < 0.001).ConclusionUltra-laser irradiation combined with gabapentin reduced pain, improved health-related quality of life, and was associated with fewer short-term adverse events compared with gabapentin alone. Confirmation with longer follow-up, sham-controlled designs, and cost-effectiveness evaluation is warranted.